Late antiretroviral refills and condomless sex in a cohort of HIV-seropositive pregnant and postpartum Kenyan women - Eastment, McKenna C. (PLoS One, 2021)
INTRODUCTION: The postpartum period can be challenging for women living with HIV. Understanding how the postpartum period impacts ART adherence and condomless sex could inform the development of comprehensive sexual and reproductive health and HIV services tailored to the needs of women living with HIV during this critical interval. METHODS: In a longitudinal cohort study of HIV-seropositive Kenyan women, late ART refills and self-reported condomless sex were compared between the woman’s pregnancy and the postpartum period. Analyses were conducted using generalized estimating equations and adjusted for alcohol use, depressive symptoms, intimate partner violence (IPV), and having a recent regular partner. Effect modification was explored for selected variables. RESULTS AND DISCUSSION: 151 women contributed visits. Late ART refills occurred at 7% (32/439) of pregnancy visits compared to 18% (178/1016) during the postpartum period (adjusted relative risk [aRR] 2.44, 95% confidence interval [CI] 1.62–3.67). This association differed by women’s education level. Women with ≥8 years of education had late ART refills more during the postpartum period than pregnancy (aRR 3.00, 95%CI 1.95–4.62). In contrast, in women with <8 years of education, late ART refills occurred similarly during pregnancy and the postpartum period (aRR 0.88, 95%CI 0.18–4.35). Women reported condomless sex at 10% (60/600) of pregnancy visits compared to 7% (72/1081) of postpartum visits (aRR 0.76, 95%CI 0.45–1.27). This association differed by whether women had experienced recent IPV. Women without recent IPV had a significant decline in condomless sex from pregnancy to postpartum (aRR 0.53, 95%CI 0.30–0.95) while women with recent IPV had no significant change in condomless sex from pregnancy to postpartum (aRR 1.76, 95%CI 0.87–3.55). CONCLUSION: Improved support for ART adherence during the postpartum period and addressing IPV to limit condomless sex could improve HIV treatment and prevention outcomes for HIV-seropositive women as well as their infants and sexual partners.